Continuous Femoral Nerve Block Reduces the Need for Manipulation Following Total Knee Arthroplasty. Issue 3 (11th July 2022) - Freccero, David M.; Van Steyn, Peter; Joslin, Patrick M.N.; Robbins, Claire E.; Li, Xinning; Efremov, Kristian; Shukla, Pinak; Talmo, Carl T.; Bono, James V.
Abstract : Background: Peripheral nerve blocks improve both pain control and functional outcomes following total knee arthroplasty (TKA). However, few studies have examined the effects of different peripheral nerve block protocols on postoperative range of motion. The present study assessed the impact of a single-shot femoral nerve block (SFNB) versus continuous femoral nerve block (CFNB) on postoperative range of motion and the need for subsequent manipulation following TKA. Methods: We retrospective reviewed patient charts to identify patients who had undergone primary elective unilateral TKA by 2 surgeons at a high-volume orthopaedic specialty hospital over a 3-year period. A total of 1, 091 patients received either SFNB or CFNB and were included in the data analysis. Identical surgical techniques, postoperative oral analgesic regimens, and rehabilitation protocols were used for all patients. Patients with <90° of flexion at 6 weeks postoperatively underwent closed manipulation under anesthesia (MUA). Results: Overall, 608 patients (55.7%) received CFNB and 483 patients (44.3%) received SFNB. Overall, 94 patients (8.6%) required postoperative manipulation for stiffness, including 36 (5.9%) in the CFNB group and 58 (12%) in the SFNB group. The 50% reduction in the need for manipulation in the CFNB group was independent of primary surgeon (p > 0.05). No significant differences were observed between the groups in terms of postoperative range of motion, either at the time of discharge or at 6 weeks postoperatively. A history of knee surgery, decreased preoperative range of motion, and decreased range of motion at the time of discharge were significantly associated with the need for further MUA (p = 0.0002, p < 0.0001, and p < 0.0001, respectively). Conclusions: Despite similar final postoperative range of motion between patients in both groups, our results suggest that CFNB may be superior to SFNB for reducing the need for postoperative manipulation after primary TKA. Furthermore, a history of ipsilateral knee surgery, decreased preoperative range of motion, and decreased range of motion at the time of discharge were identified as independent risk factors for postoperative stiffness requiring MUA after primary TKA. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.